Предмет: Алгебра,
автор: bfleck95
представить в виде многочлена
(х-5)(х-2)
(3с-4б)(2с+3б)
(4-х)(х в квадрате - 3х+5)
Ответы
Автор ответа:
0
(х-5)(х-2)=x²-5x-2x+10=x²-7x+10
(3с-4b)(2с+3b)=6c²+9bc-8bc-12b²=6c²+bc-12b²
(4-х)(х² - 3х+5)=4x²-12x+20-x³+3x²-5x=-x³+7x²-17x+20
(3с-4b)(2с+3b)=6c²+9bc-8bc-12b²=6c²+bc-12b²
(4-х)(х² - 3х+5)=4x²-12x+20-x³+3x²-5x=-x³+7x²-17x+20
Автор ответа:
0
х²-7х+10
6с²+сб-12б²
х³+7х²-17х+20
6с²+сб-12б²
х³+7х²-17х+20
Похожие вопросы
Предмет: Українська література,
автор: ritakirilcenko8
Предмет: Английский язык,
автор: artemggggh
Предмет: Музыка,
автор: abdykalykovaakylaj9
Предмет: Математика,
автор: JuliaSel
Предмет: История,
автор: Yana881